Peer Feedback in Writing: How Effective Is It for English Education Students? - Verina Widyadhana; Noeris Meiristiani; Aisyah Najwa Noviana; Arina Khoiro Salma (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This study investigates the influence of peer feedback on the writing performance of English-major students, focusing on grammatical accuracy, content development, and text coherence. It also examines the conditions that support effective peer feedback and the challenges that hinder its implementation in academic writing classes. Employing a narrative review method, this study analyzes 10 empirical research articles published between 2019 and 2024. The findings indicate that peer feedback positively enhances students’ grammatical accuracy, content organization, and overall coherence of writing. In addition, it promotes learner autonomy and helps reduce writing anxiety when supported by clear guidelines, adequate training, and teacher facilitation. The effectiveness of peer feedback is further strengthened by factors such as trust among learners and appropriate scaffolding. The review is grounded in Vygotsky’s socio-cultural theory and Swain’s output hypothesis, which emphasize the role of interaction and self-correction in language development. Despite limitations in the reviewed studies, including small sample sizes and short research durations, this review concludes that peer feedback can be as effective as teacher feedback when properly implemented. Therefore, integrating peer review systematically into writing curricula is recommended.